The Effect of Lean Green Management System and Waste Reduction Technique on Lean Green Business Results in the Automotive Manufacturing Industry - Ermawati, Eli; Anggarini, Farida Rahma; Khanza, Miranda; Restiyono, Paran; Umar, Yandi; Prabowo, Herry Agung (Proceeding Mercu Buana Conference on Industrial Engineering, 2023)
There was rapid growth in the automotive manufacturing industry as evidenced by the current increasing number of different variations of vehicles in society. This advancement requires industry players to compete effectively by optimizing their performance to achieve production capacity and gain adequate market share. This study aims to map and describe the current conditions of Lean Green Management System (LGMS) and Lean Green Waste Reduction Technique (LGWRT) implementation in the automotive manufacturing industry in Indonesia as well as to find the best model for implementing TPM and LGMS.Lean Green Management System (LGMS) and Lean Green Waste Reduction Technique (LGWRT) are the concepts associated with streamlining the activities usually conducted by companies in the manufacturing and service sectors. Therefore, this research focuses on evaluating the influence of implementing these concepts on the Lean Green Business Results of the automotive manufacturing industry. This was achieved through a multivariate statistical analysis applied to explain the harmonious continuity between the indicator and latent variables directly observed using SEM-PLS. The results showed that the application of LGMS and LGWRT has a significant and positive effect on Lean Green Business Results (LGBR) with 97.5% while the remaining 2,5% was linked to other variables. This means LGBR has been fully accepted